Urdu ka guldasta-nurgis (Oxford) - Farooqui, Fouzia Ahsan (Pakistan : Oxford University Press, 2022)
Urdu Ka Guldasta (Khususi Isha$1 (Bat): Nargis Student$1 (Bs Book for Class 4 is a vibrant, full-color Urdu textbook aligned with Pakistan$1 (Bs Single National Curriculum (2020). Authored by Fozia Ahsan Farooqui and published by Oxford University Press, this 145-page paperback (approx. 340 g) integrates structured language-learning exercises across prose and poetry. Emphasizing all four language skills$1 (Blistening, speaking, reading, and writing$1 (Bit incorporates phonics, comprehension tasks, creative writing, vocabulary building, and objective-style questions to engage students and support progressive learning. Published in 2022, it serves as a dynamic and curriculum-aligned resource for young Urdu learners.s
Keywords: Urdu - Text Book